1990
DOI: 10.1093/ajcn/52.5.858
|View full text |Cite
|
Sign up to set email alerts
|

Selenium intake, age, gender, and smoking in relation to indices of selenium status of adults residing in a seleniferous area

Abstract: Duplicate meals, serum, whole blood, and toenails were collected every 3 mo for 1 y from a group of 44 free-living adults residing in high-selenium areas of South Dakota and Wyoming to assess the relation of selenium intake to indices of selenium status. The average selenium values for the group were as follows: dietary intake, 174 +/- 91 micrograms/d (mean +/- SD), 2.33 +/- 1.08 micrograms/kg body wt; serum, 2.10 +/- 0.38 mumol/L; whole blood, 3.22 +/- 0.79 mumol/L; and toenails, 15.2 +/- 3.0 nmol/g. Selenium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
65
2
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 25 publications
15
65
2
3
Order By: Relevance
“…Our finding that current smokers have lower selenium levels than never-smokers is consistent with previous studies (Hunter et al, 1990;Swanson et al, 1990;van den Brandt et al, 1993). However, smoking was not associated with risk in this study population and additional adjustment for smoking made no appreciable difference to the association between selenium concentration and cancer risk.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding that current smokers have lower selenium levels than never-smokers is consistent with previous studies (Hunter et al, 1990;Swanson et al, 1990;van den Brandt et al, 1993). However, smoking was not associated with risk in this study population and additional adjustment for smoking made no appreciable difference to the association between selenium concentration and cancer risk.…”
Section: Discussionsupporting
confidence: 91%
“…This is in contrast to the results of the Nutritional Prevention of Cancer trial that found selenium supplementation to be associated with a significant reduction in prostate cancer risk (Clark et al, 1996;Duffield-Lillico et al, 2002). Several prospective studies have also found significant protective associations for serum or nail selenium levels in relation to prostate cancer (Yoshizawa et al, 1998;Helzlsouer et al, 2000;Nomura et al, 2000;Brooks et al, 2001;van den Brandt et al, 2003). However, consistent with the findings from the present study, some other observational studies have failed to find such an association Coates et al, 1988;Knekt et al, 1990;Hardell et al, 1995;Ghadirian et al, 2000;Goodman et al, 2001;Vogt et al, 2003).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, Lane et al (1983) failed to ®nd a statistically signi®cant correlation between these variables and Snook et al (1983) only reported a weak correlation. However, Swanson et al (1990) demonstrated a highly signi®cant relationship (r 0.51) between dietary Se, measured by direct analysis, and serum Se. The population studied had a relatively wide range of Se intakes which would increase the chance of obtaining a signi®cant correlation.…”
Section: Discussionmentioning
confidence: 96%
“…While smoking has been associated with reduced Se status (Hunter, 1990;Swanson et al, 1990) the results of studies are equivocal (Lloyd et al, 1983;Robinson et al, 1983;Olivieri et al, 1984). In this study, reported Se intake was similar in smokers and non-smokers for both sexes.…”
Section: Discussionmentioning
confidence: 99%